Why blu-ray vs. HD-DVD ist not VHS vs. Betamax: The co-evolution of standard-setting consortia - Julian P. Christ; André P. Slowak (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2009)
Extensive research has been conducted on the economics of standards in the last three decades. To date, standard-setting studies emphasize a superior role of demand-side-driven technology diffusion; these contributions assume the evolution of a user-driven momentum and network externalities. We find that consumers wait for a dominant standard if they are unable to evaluate technological supremacy. Thus, supply-side-driven activities necessarily need to address an absence of demand-side technology adoption. Our paper focuses on Blu-ray vs. HD-DVD as an illustrative case of consortia standard wars. One central role of consortia is to coordinate strategic behavior between heterogeneous agents, e.g. incumbents, complementors (content providers) and others, but also to form a coalition against other standard candidates. More precisely, we argue that agents signal standard-setting war outcomes through consortia events. We depict the essential role of consortia structures for the recently determined standard war between the High-Definition disc specifications Blu-ray and HD-DVD. Therefore, the paper suggests that unique supply-side dynamics from consortia structures, consortia announcements and exclusive backing decisions of firms determined the standard-setting process in the Blu-ray vs. HD-DVD standard war. This study is based on the following data: movie releases and sales numbers, membership affiliation for structural consortia analysis, and an in-depth event study. A detailed comparison of the technological specifications of both standard specifications supports our argument that there was no technological supremacy of one standard candidate from a consumer-oriented usecase perspective. We furthermore clarify that content providers (complementors) such as movie studios and movie rental services feature a gate-keeping position in the Blu-ray vs. HD-DVD standard war. In the case of Blu-ray, film studios decided the standard war because the availability of movie releases, but not technological supremacy, made the standard attractive to consumers. Finally, we find that there is a co-evolution of the consortia in terms of membership dynamics. Particularly, firm allegiance of heterogeneous agents plays a crucial role.
urn:nbn:de:bsz:100-opus-3668
Keywords: B52; D84; L15; O33; 330; Blu-ray; HD-DVD; standard wars; co-evolution; consortia; event study; Optischer Speicher; Videokassette; Normung; Arbeitsgemeinschaft; Wettbewerb; Evolutionsökonomik; Event Study; Welt